Brave Humanism : Black Women Rewriting the Human in the Age of Jane Crow - Godfrey, Mollie (The Ohio State University Press, 2025)
In Brave Humanism, Mollie Godfrey argues that long before the post-1960s critiques of Western humanism emerged, an earlier generation of Black women writers were committed to reclaiming and redefining the human on their own terms. For the writers under study here—Pauline Hopkins, Nella Larsen, Zora Neale Hurston, Ann Petry, Gwendolyn Brooks, and Lorraine Hansberry—narrative forms offered intellectual space to challenge the white supremacist and patriarchal logics of Western humanism that underwrote de jure segregation. Through these narratives, they worked toward their own visions of humanity and human freedom—visions that would come to inspire later generations of Black feminists. By recovering Jane Crow–era Black women writers’ undervalued intellectual work of critique and creation, Godfrey also intervenes in critical conversations about the relationships between Black creative work, Black women’s intellectual work, and our ideas about human agency and collectivity. In recovering this hidden intellectual genealogy, this book offers a more nuanced history of Black women’s engagement with the idea of the human and places a longer history of Black women’s writing at the heart of humanist and posthumanist study.